PENGARUH SEMANGAT KERJA, DISIPLIN KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA GURU SMA NEGERI 1 PAMOTAN - Rohmah, Arifatur; Tahwin, Muhammad (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This research aims to test the relationship between working spirit, working discipline, and job satisfaction on teacher performance in SMA Negeri 1 Pamotan. This study's participants are the high school teachers in SMA Negeri 1 Pamotan, totaling 32 civil servant teachers. Data was obtained from respondents with the research instrument using a questionnaire. Sampling techniques using saturated sampling or census. Data analysis techniques using multiple linear regression. The study's results show that working spirit and working discipline have a non-significant positive impact, and the study’s findings indicate that teachers' performance is significantly improved by job satisfaction. The results of the determination test for the variables working spirit, working discipline, and job satisfaction were able to explain variations in teacher performance variables of 70.1%. Keywords: Working Spirit; Working Discipline; Job Satisfaction; Teacher Performance